Search the dark - Todd, Charles. (Headline, 1999)
When a woman is murdered in a sleepy Dorset village, it appears to be a crime of passion. The killer is immediately arrested. But it is the identity of the victim that brings Inspector Rutledge down to investigate. For if the woman was the killer's wife, then where are their two children?